2004
DOI: 10.1099/mic.0.27251-0
|View full text |Cite
|
Sign up to set email alerts
|

Crotonyl-coenzyme A reductase provides methylmalonyl-CoA precursors for monensin biosynthesis by Streptomyces cinnamonensis in an oil-based extended fermentation

Abstract: It is demonstrated that crotonyl-CoA reductase (CCR) plays a significant role in providing methylmalonyl-CoA for monensin biosynthesis in oil-based 10-day fermentations of Streptomyces cinnamonensis. Under these conditions S. cinnamonensis L1, a derivative of a high-titre producing industrial strain C730.1 in which ccr has been insertionally inactivated, produces only 15 % of the monensin yield. Labelling of the coenzyme A pools using [ No labelling of the malonyl-CoA-derived positions was observed. The opposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 48 publications
2
37
1
Order By: Relevance
“…In Streptomyces, methylmalonyl-CoA and ethylmalonylCoA are two of the most common chain extender units for the biosynthesis of many polyketide antibiotics, and several pathways for their generation have been proposed (Hopwood & Sherman, 1990;Zhang & Reynolds, 2001 (Birch et al, 1993;Li et al, 2004). In addition, a meaA gene, which shares similarity with the large subunit of methylmalonyl-CoA mutase, was involved in an unknown pathway to methylmalonyl-CoA formation (Zhang & Reynolds, 2001).…”
Section: Orthologous Phx Genes In Two Streptomyces Genomesmentioning
confidence: 99%
“…In Streptomyces, methylmalonyl-CoA and ethylmalonylCoA are two of the most common chain extender units for the biosynthesis of many polyketide antibiotics, and several pathways for their generation have been proposed (Hopwood & Sherman, 1990;Zhang & Reynolds, 2001 (Birch et al, 1993;Li et al, 2004). In addition, a meaA gene, which shares similarity with the large subunit of methylmalonyl-CoA mutase, was involved in an unknown pathway to methylmalonyl-CoA formation (Zhang & Reynolds, 2001).…”
Section: Orthologous Phx Genes In Two Streptomyces Genomesmentioning
confidence: 99%
“…This observation suggested that under these growth conditions the butyryl-CoA pathway was important for providing ethylmalonyl-CoA (formed by carboxylation of butyryl-CoA) for monensin A biosynthesis, but not in methylmalonyl-CoA. More recently it has been shown that in an oil-based extended fermentation medium, there is a dramatic decrease in the methylmalonyl-CoA pool and overall titers for the L1 mutant as compared to the parent strain [11]. This observation indicates that under these conditions where the major carbon source comes from lipid degradation and enters central metabolism at the level of acetyl-CoA, the butyryl-CoA pathway provides the major route to methylmalonylCoA.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, there may be lower levels of other naturally occurring acylated PLM products which have not yet been identified from these strains. These PLMs may be generated by PlmS 3 -catalyzed acylation of PLM G with other branched-chain acyl-CoAs or straight-chain acyl-CoA substrates (butyryl-CoA and crotonyl-CoA are both known primary metabolites [16] and substrates for this enzyme).…”
Section: Discussionmentioning
confidence: 99%